Regular versus as-needed treatments for mild asthma in children, adolescents, and adults: a systematic review and network meta-analysis - Prapaporn Pornsuriyasak; Sunatee Sa-nguansai; Kunlawat Thadanipon; Pawin Numthavaj; Gareth J. McKay; John Attia; Ammarin Thakkinstian (BMC Medicine)
Abstract Background Inhaled corticosteroids (ICS) are recommended treatment for mild asthma. We aimed to update the evidence on the efficacy and safety of ICS-containing regimens, leukotriene receptor antagonists (LTRA), and tiotropium relative to as-needed (AN) short-acting β2-agonists (SABA) in children (aged 6–11 years) and adolescents/adults. Methods A systematic review of randomized controlled trials (RCTs) of regular and AN treatment for mild asthma was conducted (CRD42022352384). PubMed, Scopus, and ClinicalTrials.gov were searched up to 31st March 2024. RCTs in children or adolescents/adults with mild asthma were eligible if they compared any of the following treatments: ICS alone or in combination with fast-acting bronchodilators (FABA, i.e., formoterol or SABA) or long-acting β2-agonists (LABA), LTRA, tiotropium, and SABA alone, for the following outcomes: exacerbations, asthma symptoms, forced expiratory volume in 1 s (FEV1), asthma-specific quality-of-life (QoL), or severe adverse events (SAEs). The two-stage network meta-analysis (NMA) was used to pool risk ratios (RR) or mean differences for treatment outcomes. The risk of bias was assessed using the Revised Cochrane risk-of-bias tool for randomized trials (RoB2). This review followed the PRISMA reporting guideline and the PRISMA checklist is presented in Additional file 2. Results Thirteen RCTs in children and 29 in adolescents/adults were included. Regular ICS ranked best for preventing exacerbations and improving FEV1 in children. NMA of RCTs suggested regular ICS were better in preventing exacerbations than LTRA (RR [95% confidence intervals], (0.81 [0.69,0.96]) and AN-SABA (0.61 [0.48,0.78]), and not different from AN-ICS (0.83 [0.62,1.12]). In adolescents/adults, for preventing severe exacerbations, regular ICS outperformed AN-SABA (0.58 [0.46,0.73]), but AN-ICS/FABA (0.73 [0.54,0.97]), and regular ICS/LABA (0.68 [0.48,0.97]) surpassed regular ICS. Symptom relief and improved FEV1 were not different among the ICS-containing regimens. Regular ICS ranked best for improved QoL and least likely for SAEs. Conclusions Regular ICS use may be the most effective treatment for preventing exacerbation and increasing FEV1 in children with mild asthma. In adolescents/adults, ICS-containing regimens outperformed AN-SABA for exacerbation prevention. With varying degrees of heterogeneity, severe exacerbation risk in adolescents/adults might be lower with regular ICS/LABA or AN-ICS/FABA than regular ICS, where AN-ICS/FABA may not be suitable for patients with low FEV1. Additionally, regular ICS use may enhance FEV1 and QoL more than AN-SABA and LTRA.